2019
DOI: 10.1111/dom.13864
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sitagliptin on gastric emptying of, and the glycaemic and blood pressure responses to, a carbohydrate meal in type 2 diabetes

Abstract: Aims To determine the effects of the dipeptidyl peptidase‐4 inhibitor, sitagliptin, on gastric emptying (GE) of a high‐carbohydrate meal and associated glycaemic and blood pressure (BP) responses in type 2 diabetes mellitus (T2DM). Materials and Methods Fourteen patients with T2DM (nine men, five women; age 67.8 ± 1.5 years; body mass index 31.2 ± 0.9 kg/m2; T2DM duration: 4.2 ± 0.9 years; glycated haemoglobin: 46 ± 1.8 mmol/mol [6.4% ± 0.2%]), managed by diet and/or metformin, underwent concurrent measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 31 publications
1
17
1
Order By: Relevance
“…Fascinatingly, although case reports suggest beneficial effects of DPP‐4 inhibitors on PPH, 3,4 the available trials are conflicting. Stevens et al observed no effect on postprandial BP after two doses of sitagliptin 33 . Our own group previously showed that 12 weeks of sitagliptin versus placebo augments the postprandial drop in DBP 2 .…”
Section: Discussionmentioning
confidence: 94%
“…Fascinatingly, although case reports suggest beneficial effects of DPP‐4 inhibitors on PPH, 3,4 the available trials are conflicting. Stevens et al observed no effect on postprandial BP after two doses of sitagliptin 33 . Our own group previously showed that 12 weeks of sitagliptin versus placebo augments the postprandial drop in DBP 2 .…”
Section: Discussionmentioning
confidence: 94%
“…However, there is a lack of clinical trials on GLP-1 receptor agonists in patients with PPH. In two case reports, DPP-IV inhibitors were found to improve symptoms of dizziness after a meal and decrease blood pressure drop ( 34 , 35 ), but DPP-IV inhibitors showed no difference in gastric emptying and postprandial blood pressure compared with placebo in the new randomized crossover trial ( 36 ), so further research is necessary to confirm the mechanism of the DPP-IV curative effect. Duodenal administration of 1 g of metformin improved the frequency and degree of PPH and delayed gastric emptying in type 2 diabetic patients who were not receiving hypoglycemic medication ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…That the reduction in postprandial glycaemia induced by exogenous GLP-1 is associated with less, rather than more, postprandial insulin secretion suggests that the slowing of gastric emptying outweighs its insulinotropic effect in controlling postprandial glycaemia [ 59 ]. In contrast to the GLP-1 receptor agonists, the DPP-4 inhibitors—which prolong the half-life of endogenous GLP-1—have little, if any, effect on gastric emptying [ 60 , 61 ].…”
Section: Secretion and Actions Of Gastrointestinal Hormonesmentioning
confidence: 99%